RESPONSE OF SINGLE NODE EXPLANTS OF FIGS (FICUS CARRICA L.) SHINGALI CV. TO DIFFERENT PLANT GROWTH REGULATORS AND CULTURE MEDIA - RASHEED , KHETAM A.; TOMA, RAFAIL S. (Journal of Duhok University, 2023)
An efficient micropropagation protocol was developed for the fig tree Shingali cultivar from single node explants grown on MS and WPM enriched with different growth regulators. Healthy and aseptic cultures were achieved from the disinfestation with 1.5% mercuric chloride for 5 minutes. At initiation stage, the addition of 1.5 mg.l-1 BA was superior upon the rest of treatments by giving the highest number of shoots (4.00 shoots/ explant), the highest number of leaves (9.00 leaves/ explant) and the longest shoots (3.65 cm). The best multiplication parameters were recorded from the addition of 2.5 mg.l-1 BA to woody plant medium (WPM) enriched with 1.5 mg.l-1 GA3 by giving 7.09 shoots/ explant, 25.09 leaves/ explant and 8.44 cm as the longest shoots. On the other hand, the best rooting parameters were recorded when 0.2 mg.l-1 NAA was added to MS medium enriched with 1.5 mg.l-1 GA3 by reaching 100% rooting, 26.80 roots/ explant and 8.40 cm as the longest roots. At the acclimatization stage, the whole tested culture mixtures were able to achieve 100% survival rates of plantlets acclimatization. And using peatmoss alone was the superior culture medium at this stage by recording the highest values of plantlet height (9.50 cm), number of leaves (36.00 leaves/ plantlet and the highest number of shoots (9.00 shoots/ plantlet) after four weeks from transplanting under greenhouse conditions. In general, this micropropagation protocol is very convenient to be used for any future commercial propagation for this important fig tree cultivar in the area